A comparative study of Silodosin vs. Tamsulosin in the management of Benign Prostatic Hyperplasia: Outcomes in a tertiary care setting in Karachi. - Seerat Ul Uroos; Mohsin Anwer; Sumaiya Noor; Muhammad Rashid (International Journal of Endorsing Health Science Research, 2024)
Background: Lower urinary tract symptoms (LUTS) caused by benign prostatic hyperplasia (BPH) are prevalent among aging males, with acute urinary retention (AUR) being a common urological emergency. Alpha-blockers, such as tamsulosin and silodosin, are widely used in managing BPH-related LUTS and improving outcomes in Trial Without Catheter (TWOC). However, the comparative efficacy of these two medications remains a topic of clinical interest. This study aims to compare the efficacy of tamsulosin versus silodosin in achieving successful TWOC and improving the International Prostate Symptom Score (IPSS) in patients with BPH at a tertiary care hospital in Karachi. Methodology: A randomized controlled trial was conducted involving 100 male patients with BPH, aged 45-85 years, who were randomly assigned to two groups: Group A (silodosin, 50 patients) and Group B (tamsulosin, 50 patients). The primary outcomes included successful TWOC (defined as a post-void residual volume of <100 ml) and improvement in IPSS after one month. Statistical analyses were performed using the chi-square and Mann-Whitney U tests, with a significance level set at P ≤ 0.05. Results: In Group A, 70% of patients achieved a successful TWOC, compared to only 20% in Group B (P = 0.001). The mean IPSS score in Group A was significantly lower than in Group B (P = 0.001), indicating better symptom control with silodosin. Conclusion: Silodosin demonstrated superior efficacy in facilitating TWOC success and reducing LUTS compared to tamsulosin. These findings suggest that silodosin should be considered the preferred alpha-blocker for managing BPH, especially in patients with AUR, offering improved outcomes for both catheter removal and symptom relief.